Condições atmosféricas associadas ao furacão Catarina e a outros dois casos de estudo - Corrêa, Clóvis Roberto Levien (2010)
This work presents the study of atmospheric conditions associated the occurrence of Hurricane Catarina and two study cases. The Catarina occurred in March 2004 and reached the coast of southern Brazil.The other case studies correspond to cut-off lows that occurred in May 2005 and September 2008. It was used the WRF model, version 3.0, to obtain the meteorological fields during the period of occurrence of these events and images of the geostationary satellite GOES-12 and QuikSCAT. For Hurricane Catarina, data from surface meteorological stations were also analyzed. Initially, the study cases consisted of cut-off lows preceded by extratropical cyclones in the South Atlantic Ocean. When they shut the western flow, they occurred at the interface of different patterns of vertical variation of horizontal wind in the layer between 850-200hPa and showed closed cyclonic circulation at middle levels. At high levels, it was observed bifurcation of the jet with a trough quasi-stationnary near the southern coast of Brazil. The observed atmospheric blocking together with the thermodynamic and kinematic configurations of each case contributed to the occurrence of tropical transition and subsequent formation of Hurricane Catarina, in March 2004, while the other cut-off lows dissipated.